Lifting Titan’s veil : - Lorenz, Ralph (Cambridge University Press, 2002)
Lifting Titan's Veil is a revealing account of the second largest moon in our solar system. This world in orbit around Saturn is the only body in the solar system with an atmosphere strikingly similar to Earth's. Titan is like a giant frozen laboratory that may help scientists understand the first chemical steps towards the origin of life.